A vivência da sexualidade por adolescentes portadoras de deficiência visual - Bezerra, Camilla Pontes (2007)
Adolescence is a phase of life marked by sexual maturation and accompanied by psychological and social transformations. Although visually impaired persons are subject to the same process, literature has dedicated little attention to this theme. The combination between transformations in this phase of life, the indefiniteness they are accompanied by and the visual impairment justify a study about the sexual experience of female, visually impaired adolescents inserted in society and in the school community. We interviewed five visually impaired adolescents at a Pedagogical Support Center (PSC) for blind and/or visually impaired people. Questions attempted to find out how these adolescents perceived the cause of their visual impairment, their education level, family composition and orientations, affective-sexual experience, level of knowledge about sexuality-related issues, including contraception and sexually transmitted diseases. Results revealed that visually impaired adolescents display the same sexual development characteristics as other people, although with their own properties. The lack of vision does not decrease sexual interest, but only differentiates their curiosity about this subject: they want to get to know their body and its functioning. Like all adolescents, young people who cannot see also attempt to define their identity and place in society. Moreover, they want to discover their own sexuality, find adequate means to express their sexual impulses and experience affective relationships. We found lack of knowledge about contraceptive methods and STDs, with superficial information. In order to create a health promotion culture, knowledge accessible to this population is essential. We believe that visually impaired adolescents should take their own decisions, thus practicing their rights and obligations with a view to the full exercise of citizenship